2017
DOI: 10.3389/fpls.2017.00453
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Pennisetum glaucum Eukaryotic Translational Initiation Factor 4A (PgeIF4A) Confers Improved Drought, Salinity, and Oxidative Stress Tolerance in Groundnut

Abstract: Eukaryotic translational initiation factor 4A belong to family of helicases, involved in multifunctional activities during stress and non-stress conditions. The eIF4A gene was isolated and cloned from semi-arid cereal crop of Pennisetum glaucum. In present study, the PgeIF4A gene was expressed under the regulation of stress inducible Arabidopsis rd29A promoter in groundnut (cv JL-24) with bar as a selectable marker. The de-embryonated cotyledons were infected with Agrobacterium tumefaciens (LBA4404) carrying r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Our results showed that eIF4A was up accumulated in S. brachiata at the lower dosage and down accumulated at higher dosage. The involvement of eIF4A genes in abiotic stress tolerance has been reported for several plant species like tobacco [68], rice [69], pea [70,71], and groundnut [72]. A transgenic approach highlighted the role of eIF4A genes in abiotic stress tolerance highlighted a reduced accumulation of sodium as primary mechanism [68,73].…”
Section: Discussionmentioning
confidence: 97%
“…Our results showed that eIF4A was up accumulated in S. brachiata at the lower dosage and down accumulated at higher dosage. The involvement of eIF4A genes in abiotic stress tolerance has been reported for several plant species like tobacco [68], rice [69], pea [70,71], and groundnut [72]. A transgenic approach highlighted the role of eIF4A genes in abiotic stress tolerance highlighted a reduced accumulation of sodium as primary mechanism [68,73].…”
Section: Discussionmentioning
confidence: 97%
“…Eukaryotic translational initiation factor 4A (intronic SNP associated with SLA) belongs to the family of helicases. They can stimulate stress‐induced pathways and have been shown to increase stress tolerance in groundnut (Santosh Rama Bhadra Rao et al, 2017; Tuteja et al, 2014). Finally, ubiquitin carboxyl‐terminal hydrolases (intronic SNP associated with SLA) were found to be needed for the period maintenance of the circadian clock during high temperatures in Arabidopsis (Hayama et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The sncRNAs suppress the RNA helicase activity of IF-4A [ 91 ]. Overexpression of IF-4A results in an increased tolerance against various abiotic stresses [ 92 ], especially drought stress [ 93 ]. Since both oxidative stress and the loss of cellular water content affect the structure of RNAs, affecting RNA helicases also has a high potential in developing stress-resilient crops [ 94 ].…”
Section: Discussionmentioning
confidence: 99%